2018
DOI: 10.3747/co.25.3911
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Vascular Access for Intravenous Systemic Therapy and Risk Factors for Lymphedema in Early-Stage Breast Cancer—A Patient Survey

Abstract: BackgroundThe choice of vascular access for systemic therapy administration in breast cancer remains an area

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In contrast to Q, patients tended to increase non-con muscle thickness and echo-intensity in BB. BC patients who had undergone breast surgical intervention believe that lifting heavy objects would increase the chance of developing breast cancer-related lymphedema 59 and leading to fear and avoidance of the affected arm 60 , 61 . MBC patients tend to have lower function levels, represented as lower grip strength and a restricted shoulder range of motion 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Q, patients tended to increase non-con muscle thickness and echo-intensity in BB. BC patients who had undergone breast surgical intervention believe that lifting heavy objects would increase the chance of developing breast cancer-related lymphedema 59 and leading to fear and avoidance of the affected arm 60 , 61 . MBC patients tend to have lower function levels, represented as lower grip strength and a restricted shoulder range of motion 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The current equipoise is reflected in surveys of patients 4 and the absence of prospective clinical trial data directly comparing various forms of vascular access for chemotherapy administration in breast cancer patients. The resulting variability is of great importance, given that cvads are not only expensive, but that all types of vascular access are associated with complications and affect the patient's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was also designed to assess practice variability with respect to the modern systemic therapy regimens and perceived rates of complications for the various access techniques. In addition, given the continued presence of various "urban legends" reported by breast cancer patients about the risk for lymphedema being higher with the use of the surgical arm for blood draws, chemotherapy administration, and blood pressure measurement 4 , our survey also contained questions about risk factors for the development of lymphedema 16 . The findings emerging from the survey will be used to inform knowledge users about potential future prospective randomized trials aiming to optimize vascular access strategies in patients with early-stage breast cancer.…”
Section: Personal Communication)mentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, Burbridge and Goyal, 2016) used a validated quality of life assessment tool for data collection. However, the remaining studies utilised self-reported questionnaires and non-validated tools that had not been tested for psychometric properties or verified for internal and external validity as data collection methods (Molloy et al, 2008;Chernecky, 2001;Campbell et al, 2004;Goossens et al, 2005;Kreis et al, 2007;Johansson et al, 2009;Ignatov, et.al., 2009;Nagel et al, 2012;Goltz et al, 2013;Edström, Lindqvist and Rosengren, 2016;Burbridge and Goyal, 2016;Harrold, Martin and Scarlett, 2016;Minichsdorfer et al, 2016;Yagi et al, 2016;LeVasseur et al, 2018;Park and Lee, 2020).…”
Section: Data Collection Methodsmentioning
confidence: 99%